2023
DOI: 10.18240/ijo.2023.09.21
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and gender disparities of Chinese cataract burden and their predictions

Tian-Hong Wu,
Wei-Ming Liu,
Jian-Qing Li
et al.

Abstract: AIM: To evaluate the trends and changes in the number and rates of disability-adjusted life years (DALYs) and prevalence of cataract in China between 1990 and 2019, and to predict the trends of cataract burden from 2020 to 2030. METHODS: The Global Burden of Diseases (GBD) database was employed to collect the data on DALYs and the prevalence of cataract in China, which was distinguished by age and sex during the past three decades from 1990 to 2019, and then changes in the number and rates of cataract from 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
4
0
1
Order By: Relevance
“…Существенными причинами нарушения зрения, особенно в старшем возрасте, выступают глаукома и катаракта, представляющие распространённую возраст-ассоциированную офтальмопатологию, как в индустриальных, так и в развивающихся государствах различных континентов [1] . Так, на долю катаракты приходится почти половина всех случаев слепоты [2,3] из-за низкой доступности специализированной офтальмологической помощи для многих слоёв населения отдалённых регионов, слаборазвитой экономики, отставания медицинских технологий по лечению катаракты и низкого уровня образования [4] . По мере того, как проблемы старения становятся всё более серьёзными, заболеваемость катарактой неуклонно повышается, что ложится серьёзным бременем на отдельных людей и систему национального здравоохранения, несмотря на наличие достаточно эффективных способов хирургического лечения катаракты [5,6] .…”
Section: обоснованиеunclassified
“…Существенными причинами нарушения зрения, особенно в старшем возрасте, выступают глаукома и катаракта, представляющие распространённую возраст-ассоциированную офтальмопатологию, как в индустриальных, так и в развивающихся государствах различных континентов [1] . Так, на долю катаракты приходится почти половина всех случаев слепоты [2,3] из-за низкой доступности специализированной офтальмологической помощи для многих слоёв населения отдалённых регионов, слаборазвитой экономики, отставания медицинских технологий по лечению катаракты и низкого уровня образования [4] . По мере того, как проблемы старения становятся всё более серьёзными, заболеваемость катарактой неуклонно повышается, что ложится серьёзным бременем на отдельных людей и систему национального здравоохранения, несмотря на наличие достаточно эффективных способов хирургического лечения катаракты [5,6] .…”
Section: обоснованиеunclassified
“…With the advent of an aging society, China has experienced a steady increase in cataract prevalence. From 1990 to 2019, the total number of cataract cases in China surpassed 1.8 million, with projections indicating a continued rise in the cataract burden from 2020 to 2030 (Wu et al, 2023). Cataracts, characterized by degenerative changes in crystalline lens metabolism leading to lens opacity (Delbarre and Froussart-Maille, 2020), primarily affect the middleaged and elderly populations, with age and diabetes identified as key risk factors (Lim et al, 2020;Dai and Zhu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, individuals suffering from both cataracts and diabetes exhibit a higher susceptibility to depression compared to those with only diabetes (López Sánchez et al, 2021). While some studies suggest that male cataract patients are more likely to experience major depressive disorders (MDD) than females (Kang et al, 2023), others argue that females are at a greater risk for developing cataracts (Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published article on the role of sex and gender in eye health stated that "Sex and gender should also be prioritized for guidance on research questions and outcomes data analyses" [7] . The integration of sex and gender differences into clinical research has been shown to inform the pathogenesis of disease [8][9][10] , sex-specific risk factors [11] , patient management, and treatment protocols [12] .…”
Section: Introductionmentioning
confidence: 99%
“…In regards to cataract surgery, it is recognized that females are at a higher risk of developing cataracts than males [13][14] , possibly due to post-menopausal declining levels of estrogen [13,15] and a longer life expectancy [10,[16][17] . In developing countries, women with cataracts continue to disproportionately suffer from lack of access and worse visual outcomes post-operatively, specifically in places where cataract outcomes remain below the goal established in the World Health Assembly 2013 Global Action Plan goal [1,18] .…”
Section: Introductionmentioning
confidence: 99%